Does socioeconomic status influence students’ access to residential college and ameliorate performance discrepancies among them in China? - Gui, Pingping; Alam, Gazi Mahabubul (Springer Nature, 2024)
Education is one of the main prerequisites for a country making economic progress. A well-informed and well-functioning education system should be able to address most kinds of discrimination or privilege, ensuring that all people have equitable access to high quality education, regardless of their socioeconomic status (SES). It is noted that it cannot prevent every discrimination-related issue that arises. Residential colleges (RCs) have evolved over time in higher education. In this era of the United Nations’ Sustainable Development Goals (SDGs), it is crucial to assess whether RCs genuinely promote equal access and good quality education. Focusing on China, this study investigates whether RCs contribute to education equality or simply serve individuals from privileged socioeconomic contexts. Primarily, employing the quantitative research methods, including descriptive and grouped regression analysis, this study analyzes data from 397 RC students nationwide. The results reveal that RCs are accessible to students from different SES backgrounds, but enrollment disparities persist based on SES. Furthermore, SES does not dictate the role of RCs in academic performance among different social groups; RCs help to narrow the performance discrepancy between students from various socioeconomic backgrounds. These findings underscore the constructive role of RCs in advancing sustainable education and provide valuable insights for decision-makers aiming to get RCs to reduce education disparities. © The Author(s) 2024.